Juvenile polyposis syndrome with gastric and duodenal polyposis presenting with refractory anemia and protein-leakage gastroenteropathy in a patient with SMAD4 mutation: a case report - Kenya Nakamura; Koji Kubota; Akira Shimizu; Tsuyoshi Notake; Tomohiko Ikehara; Kentaro Umemura; Atsushi Kamachi; Takamune Goto; Hidenori Tomida; Yoshiyuki Takahashi; Tadanobu Nagaya; Takeji Umemura; et al. (Surgical Case Reports, 2024)
Abstract Background Juvenile polyposis syndrome (JPS) is an autosomal dominant, inherited disorder characterized by multiple hyperproliferative polyps of the gastrointestinal tract, particularly of the colon, rectum, and stomach. SMAD4 mutations are frequently associated with multiple polyposis of the stomach; the condition causes severe bleeding and hypoproteinemia, which may progress to severe dysplasia and adenocarcinoma formation. We report our experience with the first case of total gastrectomy with pancreaticoduodenectomy following two partial jejunectomies for JPS, who presented with refractory anemia and protein-losing gastroenteropathy due to polyposis of the stomach and duodenum. Case presentation A 33-year-old Japanese man presented with the chief complaint of shortness of breath on exertion. His family history included gastric polyposis (mother, aunt, and cousin) and cerebral infarction (grandmother). Blood testing at the initial visit indicated iron-deficiency anemia, whereas endoscopy revealed multiple polyps in the duodenum and jejunum. Genetic testing revealed a 4 bp deletion (TGAA) in exon 5 of the SMAD4 gene; two partial small bowel resections were performed, but polyps grew in the remaining stomach, duodenum, and small intestine. The patient developed hypoalbuminemia and anemia, and required central venous nutrition and blood transfusion. However, because the hyponutrition and anemia remained poorly controlled, a total gastrectomy with concomitant pancreaticoduodenectomy was performed. Malnutrition and anemia improved, and there was no polyp recurrence in the remaining intestinal tract at 18 months after the surgery. Conclusions We report a case of JPS with refractory anemia and protein-losing gastroenteropathy that was treated with total gastrectomy with concomitant pancreaticoduodenectomy. Although the surgery was highly invasive, the patient’s nutritional status and anemia improved postoperatively, and the treatment was successful. However, to determine the appropriate surgical procedure, a detailed examination of the gastrointestinal lesions and the effects of the surgical invasion on nutritional status must be undertaken.